2023
DOI: 10.1159/000529547
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Glypican-4 Is a Predictor of 24-Month Overall Survival in Metastatic Breast Cancer

Abstract: Background & objective: Endocrine treatment combined with CDK4/6 inhibitors is the preferred treatment strategy in patients presenting with ER-positive/HER2-negative breast cancer, but the clinical course remains highly variable among individual patients. There is an unmet need for prognostic or predictive biomarkers in this important group of patients. Recently, we have identified circulating glypican-4 (GPC4) as a new biomarker of inferior outcomes in patients with metastatic colorectal cancer. The impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The released GPC4, which still exhibits biological activity, is detectable in serum, making it a potential diagnostic and prognostic marker. Two clinical studies have already shown increased plasma levels of GPC4 in metastatic colorectal and breast cancer patients to be associated with poor patient survival, proposing its biomarker potential in these cancers [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The released GPC4, which still exhibits biological activity, is detectable in serum, making it a potential diagnostic and prognostic marker. Two clinical studies have already shown increased plasma levels of GPC4 in metastatic colorectal and breast cancer patients to be associated with poor patient survival, proposing its biomarker potential in these cancers [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Also, two comprehensive clinical investigations demonstrate increased levels of plasma GPC4 in colorectal and metastatic breast cancer patients [24,25]. The increased plasma level of GPC4 in these cancers was found to be associated with poor patient survival [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations